Development of Smart Weather Reporting System Based on Blynk Application for Agriculture - Muharam, Siti NurFatin; Bahari, Azlina; Zohari, Mohd Hakimi (Progress in Engineering Application and Technology, 2022)
The Smart Weather Reporting System for Agriculture is an Internet of Things-based project. IoT is one of the most frequently used terms in information technology [1]. Users can utilize the Blynk application to collect data on temperature, humidity, and rainfall to forecast specific global weather conditions despite what might be expected. However, Blynk is capable of storing and displaying data. Besides that, this Blynk can provide excellent storage for various commonly used devices, including Arduino, NodeMCU ESP8266, Raspberry Pi, and Spark Fun. Nowadays, simply watching weather news on television, reading weather reports on websites, or uploading weather apps to the Google Play Store can also assist users in staying informed about daily weather conditions. Furthermore, it uses meteorological satellites such as POES (Polar Operational Environmental Satellites) and GOES (Geostationary Operational Environmental Satellite) that have been in orbit for an extended period to determine all of these weather conditions. Some even develop their meteorological systems, incurring relatively high market costs. As a result, of the existence of this project, which was implemented at a low cost, it is capable of detecting changes in weather conditions in the surrounding environment. However, this project will connect several detectors to the NodeMCU ESP8266 module. One of the apparent benefits is that users have access to the weather in their immediate environment. Other than that, the project will assist users in sending data to the internet with specific weather parameters via the IoT concept, utilizing platforms such as Blynk, and will notify users when the weather is bright or dark or when the soil is moist or dry. Lastly, the Blynk app is used to send and receive data, which can be viewed directly on a mobile phone or by monitoring weather parameters. Thus, it enables users to gain faster and more efficient access to their data.